(untitled) (LACCEI, 2024)
Agility and adaptation to change through methodologies or frameworks have attracted the interest of companies and organizations, however, the role played by process management has become key for a successful implementation, taking into account consideration to the interested parties, be it the client or the parties involved. Companies seek effectiveness and efficiency in the activities carried out to improve their activities or processes and what better way to face these challenges with innovation. That is why a Framework (work framework) has been designed that is the product of the integration between process management (BPM) and the Design Thinking methodology that helps to discover insights and solve problems with innovation, this framework will optimize the process of monitoring and control in the area of project quality, helping to optimize the effectiveness of the same area and the personnel involved. In the results, improvements were obtained in the monitoring and control process, improving the participation and commitment of the client, an increase in the rate of scheduled appointments was seen, which rose to 72%, in addition to the increase in the NPS satisfaction index. which managed to reach 88% with an increase in promoters and also managed to considerably reduce complaints in the area of project quality.